The Use of Genetic Information in the Implementation of Insurance: Current Problems and Prospects for their Solution - Nikiforov, Vladimir; Suvorova, Ekaterina; Zenin, Sergey (Medicine, Law & Society, 2020)
Increasing the efficiency of risk assessment for the purposes of personal insurance is impossible without using the latest achievements of modern science. This translates into a growing interest in the use of genetic research results by insurers, which manifests itself not only in legislation and insurers’ practices, but also in international recommendations on personal medical data processing for insurance purposes. Based on analysis of foreign practices, the authors determine priority areas of respective legislation development, in particular, legislative recognition of a ban on insurers’ access to genetic data in the context of obligatory medical insurance and group insurance programs; granting insurers the right to use genetic testing results for the purposes of life insurance, personal accident and sickness insurance, voluntary medical insurance, if the sum insured exceeds a statutory threshold. The reported study was funded by Russian Foundation for Basic Research (RFBR) according to Research Project No. 18-29-14056.